Once-a-Day Trazodone in the Treatment of Depression in Routine Clinical Practice - Češková, Eva; Šedová, Michaela; Kellnerová, Renata; Starobová, Olga (Pharmacology, 2018)
OBJECTIVE: The aim of the study was to evaluate the efficacy, tolerability, and safety of once-a day trazodone tablets (Trittico Prolong® 300 mg) in patients with moderate to severe depression in routine clinical practice. METHODS: Men and women ≥18 years old with Montgomery-Åsberg Depression Rating Scale (MADRS) scores > 21 and Clinical Global Impression - Severity (CGI/S) ≥4 were included in this post-authorization, non-interventional, observational prospective safety study, conducted in 8 psychiatric centers in the Czech -Republic. The acute treatment phase lasted 5 weeks: 1 week of titration and 4 weeks of full-dose treatment. Patients had follow-up visits 9 and 21 weeks after commencing -treatment. RESULTS: Overall, 85 patients were enrolled in the study, of which 80 completed the acute treatment of 5 weeks. There were significant decreases in the overall MADRS score from the baseline mean value of 27.4-21.2 at week 1 (p < 0.001), and a further decrease to 7.9 at week 5 (p < 0.001). The severity of depression according to CGI/S gradually declined. Most patients reported improvement after 6 days of trazodone treatment. The most frequent adverse drug reactions (ADRs) reported were somnolence and fatigue. CONCLUSIONS: Trazodone, in the new extended-release formulation, had very good effects in clinical practice, both in previously untreated depressive episodes and in episodes not responsive to previous antidepressive therapy.
Keywords: Drug-Related Side Effects and Adverse Reactions; antidepresiva druhé generace; Humans; lidé středního věku; Antidepressive Agents, Second-Generation; selektivní inhibitory zpětného vychytávání serotoninu; Drug Administration Schedule; Trazodone; Female; Aged; dospělí; trazodon; Psychiatric Status Rating Scales; Individualized treatment; senioři; lidé; nežádoucí účinky léčiv; Selective Serotonin Reuptake Inhibitors; Treatment-resistant depression; Adult; ženské pohlaví; psychiatrické posuzovací škály; Male; Middle Aged; Multimodal antidepressant; Depression; Clinical practice; mužské pohlaví; prospektivní studie; deprese; Serotonin Uptake Inhibitors; rozvrh dávkování léků; Prospective Studies